ANALISIS TINGKAT INTERFERENSI BAHASA INDONESIA PADA ANAK USIA 12 TAHUN BERDASARKAN PERBEDAAN LATAR BELAKANG BAHASA ORANG TUA - Regina Rendi Ardila; Ansellyta Agustine; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Language as an integral part of culture can not be separated from the problem, interdependence between languages must occur for example the language vocabulary in question, given the vocabulary has an open nature. Interference is a mistake caused by the tendency to accustom speech or speech of a language to other languages including the pronunciation of sound units, grammar, and vocabulary. Of errors that occur as a result of the engagement of the habits of speech into the second dialect language. Such as those from two different parent language backgrounds, namely Sundanese and Indonesian languages from those studied. The parent language is very influential on the child. If parents are accustomed to using the first language, so that the language of the child will follow the language of the parents, not only influential parents’ language, environment and school also greatly affect the child’s language. In children aged 12 years their language is increasing due to environmental and school factors, but the background language of parents is not lost from the child’s language. Interference factors that affect the language of the child in use.